Artisanal and Small-Scale Gold Mining (ASGM) Related Environmental and Health Problems - Sakakibara, Masayuki; Kyaw, Win Thiri; Rivera Parra, José Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on artisanal and small-scale gold mining (ASGM) all over the world, as well as its impact on the economy, environment, and health, providing sustainable solutions to severe ASGM problems. This book presents a total of 20 published articles of regions including Southeast Asia, South America, and South Africa, as well as a general overview of ASGM issues. Studies included in this book posit that (1) ASGM activity is still widely practiced as an alternative livelihood in rural areas in many countries around the world, using toxic elements such as Hg and cyanide due to a lack of legal enforcement on the ASGM sector; (2) ASGM has a negative impact on environmental ecosystems, causes occupational health problems for miners, and causes chronic health disorders in both ASGM communities and those living far from ASGM areas. However, some studies propose that specific potential bioindicators could be used to monitor the environment and health of those living in ASGM communities, providing sustainable solutions to severe ASGM problems.